Heterogeneous Consumers and Fiscal Policy Shocks. Issue 8 (16th December 2016) - ANDERSON, EMILY; INOUE, ATSUSHI; ROSSI, BARBARA
Abstract : This paper studies empirical facts regarding the effects of unexpected changes in aggregate macroeconomic fiscal policies on consumers that differ depending on individual characteristics. We use data from the Consumption Expenditure Survey to estimate individual‐level responses and multipliers for government spending. We find that unexpected fiscal shocks have substantially different effects on consumers depending on their income and age levels: the wealthiest individuals tend to behave according to predictions of standard Real Business Cycle (RBC) models, whereas the poorest ones behave according to standard IS–LM (non‐Ricardian) models, most likely due to credit constraints. Furthermore, government spending policy shocks tend to decrease consumption inequality.